Determination of Total Phenolic, Total Flavonoid and Antioxidant Activity of Batak Onion Extract (Allium chinense G. Don) (Indonesian Journal of Chemical Science, 2022)
Free radicals trigger the emergence of degenerative diseases. This disease can be suppressed by antioxidant compounds that are able to destroy and neutralize free radicals. Antioxidants can be found in the genus Allium or onions, one of which is the Batak onion. The purpose of this study was to determine total phenolic, total flavonoid and antioxidant activity of Batak onion extract. Sample extraction was carried out by multilevel maceration technique using three solvents with different polarities, namely dichloromethane, ethyl acetate and 96% ethanol. The stage of sample testing included analysis of total phenolics using the Folin-Ciocalteu method, total flavonoids were determined by the AlCl3 colorimetric method and antioxidant activity determined by the DPPH method (2,2-diphenyl-1-picrylhydrazyl). The results showed that dichloromethane extract and ethyl acetate extract did not contain flavonoid and phenolic compounds. The total content of phenolic compounds in 96% ethanol extract is 1,6800 mg GAE/g extract (classified as low). The total content of flavonoid compounds in 96% ethanol extract is 1,5467 mg QE/g extract. The antioxidant activity is indicated by IC50 value in 96% ethanol extract which was 248,9503 ppm (classified as medium) and dichloromethane extract of 412,4689 ppm (weak).